2021
DOI: 10.1016/j.tvr.2021.200227
|View full text |Cite
|
Sign up to set email alerts
|

Potential entry receptors for human γ-herpesvirus into epithelial cells: A plausible therapeutic target for viral infections

Abstract: Herpesviruses are ubiquitous viruses, specifically the Epstein Barr virus (EBV). EBV and Kaposi's sarcoma-associated herpesvirus (KSHV) establish their latency for a long period in B-cells and their reactivation instigates dreadful diseases from cancer to neurological modalities. The envelope glycoprotein of these viruses makes an attachment with several host receptors. For instance; glycoprotein 350/220, gp42, gHgL and gB of EBV establish an attachment with CD21, HLA-DR, Ephs, and other receptor molecules to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 165 publications
(243 reference statements)
0
5
0
Order By: Relevance
“…EBV treatment induced HSP-90β expression in a time-dependent manner, and HSP-90 inhibitors, 17-AAG and GA, decreased the levels of the host receptor EphA2 in a dose-dependent manner. EphA2 has been identified as a host receptor or co-factors for several viruses, including EBV, 10,11 KSHV, 27 and hepatitis C virus. 28 It has also been reported that HSP-90 inhibitors, such as 17-DMAG, 17-AAG, or Ganetespib could kill Epstein-Barr virus (EBV)-infected cells by reducing the level of EBV EBNA-1 and/or LMP1, which Lysates from HEK293T cells transiently cotransfected with HA-Ub, TRIM26-Flag, and Myc-HSP-90AB1 were subjected to immunoprecipitation with Myc antibody followed by immunoblot analysis.…”
Section: Discussionmentioning
confidence: 99%
“…EBV treatment induced HSP-90β expression in a time-dependent manner, and HSP-90 inhibitors, 17-AAG and GA, decreased the levels of the host receptor EphA2 in a dose-dependent manner. EphA2 has been identified as a host receptor or co-factors for several viruses, including EBV, 10,11 KSHV, 27 and hepatitis C virus. 28 It has also been reported that HSP-90 inhibitors, such as 17-DMAG, 17-AAG, or Ganetespib could kill Epstein-Barr virus (EBV)-infected cells by reducing the level of EBV EBNA-1 and/or LMP1, which Lysates from HEK293T cells transiently cotransfected with HA-Ub, TRIM26-Flag, and Myc-HSP-90AB1 were subjected to immunoprecipitation with Myc antibody followed by immunoblot analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Gp350 is a highly glycosylated protein that is 901 amino acids long, with half of its mass being carbohydrate. Gp350 makes an initial connection to B lymphocytes by binding to their complement receptor type 2 (CR2) or CD21, respectively [15]. CR2 is a transmembrane protein found on B lymphocytes, T lymphocytes, and follicular dendritic cells; moreover, it plays a role in the development of humoral immunity response [16].…”
Section: Ebv Replication Cyclementioning
confidence: 99%
“…EBV infects B lymphocytes through the binding of the viral glycoprotein gp350 to the high-affinity receptor CD21, followed by binding of gp42 to HLA class II molecules, resulting in membrane fusion[ 17 ]. In contrast, when low-affinity co-receptors are used to infect CD21-negative epithelial cells, the infection efficiency is extremely low (Figure 1 ).…”
Section: Ebv Infection Of Epithelial Cellsmentioning
confidence: 99%